Students' Attitudes Toward The Indonesian Language: A Study Of Students At Smpn 01 Karang Gede Empat Lawang Regency - Gina Sonia; A. Suradi; Dina Putri Juni Astuti (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to describe the Indonesian language attitudes of eighth-grade students at SMPN 01 Karang Gede Village, Sikap Dalam Subdistrict, Empat Lawang Regency, focusing on language loyalty, language pride, and awareness of language norms. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed the Miles, Huberman, and Saldaña model, consisting of data reduction, data display, and conclusion drawing.The findings reveal that students’ Indonesian language attitudes are generally in a fairly good category but not yet optimal. In terms of language loyalty, students use Indonesian in formal situations but tend to use the local language in informal interactions. Regarding language pride, students understand the importance of Indonesian as the national language, but it has not yet fully become part of their linguistic identity. In terms of language norm awareness, students still face difficulties in using Indonesian according to standard grammatical rules. Overall, students’ language attitudes are situational and strongly influenced by their social environment.